Improving the Professionalism of Madrasah Teachers Post Covid-19 - Daulay , Khoiriyah; Ritonga, Muhammad Arifin (Itqan: Jurnal Ilmu-ilmu Kependidikan, 2022)
Covid-19 has had a significant impact on the paradigm shift in Madrasah management. Currently, madrasah managers are aware of the importance of technology-based innovation. This study attempts to analyze the madrasah development model. This type of research is qualitative with a descriptive method. Data were collected through in-depth interviews with the Principal, Curriculum Deputy, Teachers, and several students. The results of the study show that madrasah innovations that are based on increasing the effectiveness of learning are carried out through optimizing managerial functions. Analysis of the online learning phenomenon is observed through the implementation stage, potential challenges, and proposed solutions. The results also show that professional teachers in carrying out their roles as teachers of students and learning are in a good category, indicated by 75%. Meanwhile, 25% of teachers cannot be categorized as professionals. This figure shows the teacher's performance is very good referring to the attitude of professionalism in the learning process. The research implies that madrasah management requires public partnerships and the involvement of many parties on an ongoing basis.